2008
DOI: 10.1007/s11121-008-0117-6
|View full text |Cite
|
Sign up to set email alerts
|

Do Predictors of the Implementation Quality of School-Based Prevention Programs Differ by Program Type?

Abstract: Research has indicated that the effectiveness of school-based prevention programs is affected by the implementation quality of these programs. As the importance of implementation has become clear, researchers have identified factors that appear to be related to implementation quality, including local program selection and training, integration into school operations, organizational capacity, principal support, and program standardization; however, it is unknown whether the impact of these factors differs by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 43 publications
6
42
2
5
Order By: Relevance
“…Previous research showed that the predictors ' effects on program implementation process and outcomes would vary across contexts (14,15) . Underestimation of the multiple ecological factors might limit the generalization of positive intervention fi ndings in real world practice (16) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that the predictors ' effects on program implementation process and outcomes would vary across contexts (14,15) . Underestimation of the multiple ecological factors might limit the generalization of positive intervention fi ndings in real world practice (16) .…”
Section: Introductionmentioning
confidence: 99%
“…Estes estudos buscaram sinalizar a efetividade e qualidade dos programas de prevenção e enfrentamento da violência realizados em espaços escolares (FARRELL, 2001;GOTTFREDSON;GOTTFREDSON, 2002;MYTTON et al, 2002;HUMPHRIES;KEENAN, 2006;OZER, 2006;PARK-HIGGERSON et al, 2008;PAYNE, 2009;ECKERT, 2010;SALGADO et al, 2014;THOMPKINS et al, 2014).…”
Section: ) Estudos De Revisão Da Literatura Sobre a Qualidade E A Efunclassified
“…This attitude become clear at an early project stage and can determine the sustainability of program use, e. g. in schools (Payne 2009;Tibbits et al 2010). Agreements or voluntary self-commitments, a continuous flow of information, the appointment of responsible parties or contact persons and their substitutes, and the allocation of working time for the task are central methods to commit the entire organization (GKV-Spitzenverband 2010; Ströbl et al 2009).…”
Section: Organizational and Leadership Supportmentioning
confidence: 99%